(Pro)renin receptor accelerates development of sarcopenia via activation of Wnt/YAP signaling axis. Issue 5 (8th July 2019) - Yoshida, Naohiro; Endo, Jin; Kinouchi, Kenichiro; Kitakata, Hiroki; Moriyama, Hidenori; Kataoka, Masaharu; Yamamoto, Tsunehisa; Shirakawa, Kohsuke; Morimoto, Satoshi; Nishiyama, Akira; Hashiguchi, Akihiro; Higuchi, Itsuro; et al.
Abstract: To extend life expectancy and ensure healthy aging, it is crucial to prevent and minimize age‐induced skeletal muscle atrophy, also known as sarcopenia. However, the disease's molecular mechanism remains unclear. The age‐related Wnt/β‐catenin signaling pathway has been recently shown to be activated by the (pro)renin receptor ((P)RR). We report here that (P)RR expression was increased in the atrophied skeletal muscles of aged mice and humans. Therefore, we developed a gain‐of‐function model of age‐related sarcopenia via transgenic expression of (P)RR under control of the CAG promoter. Consistent with our hypothesis, (P)RR‐Tg mice died early and exhibited muscle atrophy with histological features of sarcopenia. Moreover, Wnt/β‐catenin signaling was activated and the regenerative capacity of muscle progenitor cells after cardiotoxin injury was impaired due to cell fusion failure in (P)RR‐Tg mice. In vitro forced expression of (P)RR protein in C2C12 myoblast cells suppressed myotube formation by activating Wnt/β‐catenin signaling. Administration of Dickkopf‐related protein 1, an inhibitor of Wnt/β‐catenin signaling, and anti‐(P)RR neutralizing antibody, which inhibits binding of (P)RR to the Wnt receptor, significantly improved sarcopenia in (P)RR‐Tg mice. Furthermore, the use of anti‐(P)RR neutralizing antibodies significantly improved the regenerative ability of skeletal muscle in aged mice. Finally, we show that Yes‐associated protein (YAP) signaling, which is coordinately regulated by Wnt/β‐catenin, contributed to the development of (P)RR‐induced sarcopenia. The present study demonstrates the use of (P)RR‐Tg mice as a novel sarcopenia model, and shows that (P)RR‐Wnt‐YAP signaling plays a pivotal role in the pathogenesis of this disease. Abstract : (P)RR is increased in atrophied muscle with aging. (P)RR‐Tg mice showed sarcopenia like phenotype. (P)RR in muscles activated both the Wnt and YAP signaling pathways, resulting in disturbed skeletal muscle growth via impairment of myoblast fusion.